Demographic Study of Varicella Zoster Virus in Cerebrospinal Fluid ofStroke Patients in Thi-Qar Province - Zeena Fahail; Bushra Jabbar Hamad (مجلة علوم ذي قار)
Varicella Zoster Virus (VZV), also known as alpha herpesvirus Virus 3, belongs to the Alpha Herpesviridae family and is a unique virus that can reactivate neurons and root ganglia in the nervous system and causes many neurological diseases, especially stroke. Molecular and genetic studies of viruses are valuable tools for virus development and identifying viral treatments to combat the disease.  The study aims to demonstrate the causal roles of Varicella-zoster virus in the progression of stroke by detecting the presence of virus DNA in the patients CSF by real-time PCR technique. The study aimed to identify the relationship between VZV infection and demographic characteristics.